Tekstuelle bistrukturer - definition og funktion - Bernhardt, Lise (HERMES - Journal of Language and Communication in Business, 2003)
A text can be divided into a main line and “someting else”, which is not part of the main line. The main line, which may also be called the main structure of the text, has been defined on various occasions by the use of such terms as “chronological development”, “foreground”, etc. Furthermore, it has been described as the skeleton of the text. Those parts which are not main structure, and which may be called side structures, have until now only been defined negatively as not being main structure. This article describes the German researcher Christiane von Stutterheim’s definition of main- and side structures. After this it suggests an alternative definition, which pro-vides more insight about side structures, beside the fact that they are not main structure. To reach a more complete description of side structures, this article analyses the functions that side structures have in texts.